Asymmetric aminohydroxylation route to (+)-L-733,060 - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2005)
An enantioselective synthesis of (+)-L-733,060 starting from cinnamic acid using Sharpless asymmetric aminohydroxylation and Wittig reactions as the key steps is described. (c) 2005 Elsevier Ltd. All rights reserved.

Asymmetric synthesis of (-)-alpha-conhydrine - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2005)
The enantioselective synthesis of (-)-alpha-conhydrine has been achieved by two different synthetic routes. The key steps include Sharpless asymmetric dihydroxylation, regioselective opening of a cyclic sulfate and Wittig olefination. (c) 2005 Elsevier Ltd. All rights reserved.

Asymmetric synthesis of both the enantiomers of trans-3-hydroxypipecolic acid - Kumar, Pradeep; Bodas, Mandar S. (Journal of Organic Chemistry, 2005)
Both the enantiomers of trans -3-hydroxypipecolic acid have been synthesized employing the Sharpless asymmetric di-hydroxylation and epoxidation as the key steps starting from a commercially available starting material 1,4-butanediol.

Asymmetric aminohydroxylation route to cis-2,6-disubstituted piperidine-3-ol: application to the synthesis of (-)-deoxocassine - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron, 2006)
A highly efficient, flexible, and convergent route to cis-2,3,6-trisubstituted piperidines has been developed employing the Sharpless asymmetric aminohydroxylation and stereoselective reductive amination by catalytic hydrogenation as the key steps. Its usage is illustrated by the short synthesis of the piperidine-3-ol alkaloid, (-)-deoxocassine. (c) 2006 Elsevier Ltd. All rights reserved.

Asymmetric dihydroxylation route towards the synthesis of (R)-clorprenaline hydrochloride - Pandey, Rajesh Kumar; Upadhyay, Rajesh Kumar; Kumar, Pradeep (Arkivoc, 2006)
An efficient asymmetric synthesis of enantiomerically pure (R)-clorprenaline hydrochloride is described using Sharpless asymmetric dihydroxylation as the key step.

Application of hydrolytic kinetic resolution (HKR) in the synthesis of bioactive compounds - Kumar, Pradeep; Naidu, Vasudeva; Gupta, Priti (Tetrahedron, 2007)
Keywords: Biological activity; bis-epoxides; Hydrolytic kinetic resolution; meso-epoxides; Natural products; synthesis; terminal epoxides

Asymmetric dihydroxylation route to (-)-bulgecinine - Show, Krishanu; Upadhyay, Puspesh K.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2011)
The stereoselective synthesis of (-)-bulgecinine is reported from L-aspartic acid using Sharpless asymmetric dihydroxylation and intramolecular cyclization via nucleophilic displacement of alpha-tosylate as key steps. (C) 2011 Elsevier Ltd. All rights reserved.

Asymmetric routes to pentadec-1-en-4-ol: application to the syntheses of aculeatins F and epi-F, (R)- and (S)-5-hexadecanolide and a formal synthesis of solenopsin - Harbindu, Anand; Sharma, Brijesh M.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2013)
A short and simple route to the synthesis of pentadec-1-en-4-ol, an important synthetic building block for the aculeatins F and epi-F, insect pheromone 5-hexadecanolide, solenopsin and various other natural products has been developed via proline-catalyzed alpha-aminoxylation of an aldehyde and hydrolytic kinetic resolution of a terminal epoxide. While the synthesis of aculeatins F and epi-F has been accomplished using a FIFA promoted oxidative spirocyclization/dithiane deprotection reaction sequence and linchpin coupling as key steps, the synthesis of hexadecanolide and a formal synthesis of solenopsin was performed using ring-closing metathesis (RCM) as key step. (C) 2013 Elsevier Ltd. All rights reserved.

Acidic handle assemble heterogeneous carbocatalyst for facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Pandole, Satish; Suryavanshi, Amol; Kumar, Pradeep; Gajbhiye, Jayan M. (ChemistrySelect, 2019)
Acidic handle (-SO3H) assemble carbonaceous catalyst synthesized from glucose acts as a modulator for the nucleophilic fluorination reaction. The heterogeneous catalyst works with various alkyl sulfonate, halide and metal fluoride (MF), to offer a high yield of fluorinated products up to 93%. This carbonaceous catalyst is recyclable for more than five times, with no major loss of activity.
Keywords: fluorination; heterogeneous catalysis